Early Intervention Strategies to Support Mental Health and Social Development in Children - Diny Kristianty Wardany (International Journal of Education and Humanities, 2024)
This research aims to explore the effectiveness of early intervention strategies in supporting the mental health and social development of young children through a qualitative approach. The problem addressed in this study is the lack of in-depth understanding regarding the experiences of children, parents, and educators in implementing early interventions in preschool settings. To achieve this objective, the study utilizes a case study method with in-depth interviews, participatory observation, and document analysis in three preschools that have implemented intervention programs and selected through purposive sampling technique to ensure diversity of experiences and perceptions. The findings indicate that interventions involving structured play therapy, parent-child interaction sessions, and teacher-led social skills training contribute positively to enhancing children's emotional regulation and social abilities. Children show improvements in managing emotions and interacting with their peers. Parents and educators report increased confidence in children's communication and collaboration skills. Based on these findings, it is recommended that preschools integrate these intervention strategies more widely and systematically into their curricula. This research also suggests the development of ongoing training for educators on effective early intervention practices to strengthen their capacity to support comprehensive child development